Pelatihan Pemanfaatan Web Bagi Pemuda Muhammadiyah Cabang Kartasura - Azizah Fatmawati (Universitas Muhammadiyah Surakarta, 2010)
Web is one medium that can be used by many activists in communityorganizations to actualize themselves and communicate effectively. Web UtilizationTraining for Muhammadiyah Youth in Kartasura branch is expected to provideknowledge into the importance of mastering Information Technology and increasethe understanding of the web (Web Logs) as the more effective information tool (AmarMa’ruf Nahi Munkar). The result shows that the implementation of the training isquite successful. This can be seen from the enthusiasm of the participants in providingfeedback from the questionnaires delivered before and after the training. Furthermore,the training also shows an increasing knowledge in the use of the web as much as64%.